2018
DOI: 10.1016/j.rmed.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Pleural manometry–historical background, rationale for use and methods of measurement

Abstract: Subatmospheric pleural pressure (Ppl), which is approximately -3 to -5 cmHO at functional residual capacity (FRC) makes pleura a unique organ in the human body. The negative Ppl is critical for maintaining the lungs in a properly inflated state and for proper blood circulation within the thorax. Significant and sudden pleural pressure changes associated with major pleural pathologies, as well as therapeutic interventions may be associated with life-threatening complications. The pleural pressure may show two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…However, if no complications occur within 2 h from the procedure, the patient is allowed to leave the health-care facility (in an upright position). In a healthy human in an upright position, the pleural pressure is most negative in the apical parts and least negative in the basal parts of the pleural space [6]. A second point is that the alveoli in the upper parts of the lung are larger than those in the lower parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, if no complications occur within 2 h from the procedure, the patient is allowed to leave the health-care facility (in an upright position). In a healthy human in an upright position, the pleural pressure is most negative in the apical parts and least negative in the basal parts of the pleural space [6]. A second point is that the alveoli in the upper parts of the lung are larger than those in the lower parts.…”
Section: Introductionmentioning
confidence: 99%
“…The PPP analysis requires a sensitive pleural manometer enabling measurement and registration of instantaneous pleural pressure. Therefore, it could have not been done with a simple water manometer or an overdamped water manometer used in earlier studies [24]. This shows that modern, sensitive, electronic manometers can still provide new data that shed light on pleural pathophysiology and interactions between pleural cavity, as well as lung and heart functions [25].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the authors of one recent study in which an electronic tracking of pleural pressure was applied suggested that cough during therapeutic thoracentesis could exert a beneficial effect by producing an increase of pleural pressure and preventing an excessive pleural pressure decrease during pleural fluid withdrawal [26]. The advances in technical solutions applied in new pleural manometers have largely contributed to a growing interest in using pleural manometry in patients with pleural effusion [24,27]. Currently, two major directions in the studies on pleural manometry can be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding studies on mechanical ventilation, direct measurement of P pl is usually restricted to animal or cadaver studies and is typically described as not feasible in clinical practice [2]. In 2018, a detailed review by Zielinska-Krawczyk et al revealed that regarding therapeutic thoracenteses literature on direct pleural manometry actually is quite copious [4]. Direct pleural manometry has been used for studying various pathophysiological aspects of thoracentesis including the safety of high-volume pleural fluid removal.…”
mentioning
confidence: 99%
“…The catheter tip then usually lies dorsally in the middle to caudal section of the pleural cavity, with position controlled by chest radiography and sonography. Awareness of catheter tip position is fundamental for adequate interpretation of measured pressures, as is the fact that pleural surface pressure may differ from pleural fluid pressure [4]. Measurements can be intermittently displayed on our standard ICU monitor as a pressure curve for example, monitoring also negative values (Fig.…”
mentioning
confidence: 99%